2006
DOI: 10.1016/j.yexcr.2005.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of p87C3G, a novel, truncated C3G isoform that is overexpressed in chronic myeloid leukemia and interacts with Bcr-Abl

Abstract: A novel C3G isoform, designated p87C3G, lacking the most amino terminal region of the cognate protein has been found to be overexpressed in two CML cell lines, K562 and Boff 210, both expressing Bcr-Abl p210. p87C3G expression is also highly augmented in patients diagnosed with chronic myeloid leukemia (CML) Ph+, in comparison with healthy individuals, and returns to basal levels after treatment with STI571. p87C3G co-immunoprecipitates with both CrkL and Bcr-Abl in CML cell lines and co-immunoprecipitation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 34 publications
(51 reference statements)
4
41
0
3
Order By: Relevance
“…In Bcr-Abl-expressing leukaemic cells, phosphorylation was seen on p87C3G, a splice variant and not on fulllength C3G (Gutierrez-Berzal et al, 2006). Our results implicate differences in c-Abl and Bcr-Abl to engage and phosphorylate C3G.…”
Section: Discussionmentioning
confidence: 55%
“…In Bcr-Abl-expressing leukaemic cells, phosphorylation was seen on p87C3G, a splice variant and not on fulllength C3G (Gutierrez-Berzal et al, 2006). Our results implicate differences in c-Abl and Bcr-Abl to engage and phosphorylate C3G.…”
Section: Discussionmentioning
confidence: 55%
“…K562, a human cell line derived from a patient with CML, was obtained from the ATCC (CCL 243). Boff 210 cells express p210 BCR-ABL constitutively and derive from the BaF/3 murine hematopoietic cell line, as previously described (24). Authentication of BM-MNC was performed analyzing BCR-ABL expression by PCR, or BCR-ABL protein expression in K562 and Boff 210 cells by immunoblotting, every 3 to 4 months.…”
Section: Cell Culturesmentioning
confidence: 99%
“…The pGST-C3G and pGST-SH3b were gifts of C. Guerrero (Universidad de Salamanca-Consejo Superior de Investigaciones Cientificas, Salamanca, Spain) (17). GSTisomerase vectors were gifts of J. Bolstad and W. Chen (University of Calgary, Calgary, AB, Canada) (human [h]FKBP12 and hFKBP12.6), T. Ratajczak (University of Western Australia, Crawley, WA, Australia) (hFKBP51 and hCyp40), B. Chambraud (INSERM U488, Paris, France) (hFKBP52), M. Emerman (University of Washington, Seattle, WA) (hCypA), and J. Buchner (University of Technology, Munich, Germany) (hCyp40).…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
“…To distinguish between these two potential mechanisms, we precultured Jurkat T cell lysates for 24 h in the presence or absence of immunophilin inhibitors, CsA and/or FK506, and pulled down binding proteins using bead-immobilized GST-C3G or GST-SH3b [a truncated C3G corresponding to aa 208-662, which possesses multiple copies of proline-rich regions (17,33)] fusion proteins. Immunoblot analysis revealed that each of the two fusion proteins, GST-C3G and -SH3b, pulled down both CrkI and CrkII (Fig.…”
Section: Ppiase-mediated Increase In Crkii Binding To C3g Is Dependenmentioning
confidence: 99%